3D micromixer for nanoliposome synthesis: a promising advance in high mass productivity. Issue 15 (17th June 2021) - Firmino, Priscilla C. O. S.; Vianna, Sávio S. V.; da Costa, Ohanna M. M. M.; Malfatti-Gasperini, Antônio A.; Gobbi, Angelo L.; Lima, Renato S.; de la Torre, Lucimara G.
Abstract : Synthesis of unilamellar and highly monodisperse liposomes in a 3D chaotic-advection microdevice. Process of high mass productivity in which mixing conditions are not the only parameter to control liposome synthesis. Abstract : This paper addresses an important breakthrough in the high mass production of liposomes by microfluidics technology. We investigated the synthesis of liposomes using a high flow rate microfluidic device (HFR-MD) with a 3D-twisted cross-sectional microchannel to favor chaotic advection. A simple construction scaffold technique was used to manufacture the HFR-MD. The synthesis of liposomes combined the effects of high flow and high concentration of lipids, resulting in high mass productivity (2.27 g of lipid per h) which, to our knowledge, has never been registered by only one microdevice. We assessed the effects of the flow rate ratio (FRR), total flow rate (TFR), and lipid concentration on the liposome physicochemical properties. HFR-MD liposomes were monodisperse (0.074) with a size around 100 nm under the condition of an FRR of 1 (50% v/v ethanol) and TFR of 5 ml min −1 (expandable to 10 ml min −1 ). We demonstrated that the mixing conditions are not the only parameter controlling liposome synthesis using experimental and computational fluid dynamics analysis. A vacuum concentrator was used for ethanol removal, and there is no further modification after processing in accordance with the structural (SAXS) and morphological (cryo-TEM) analysis. Hence, the HFR-MD can be used to prepare nanoliposomes. It emerges as an innovative tool with high mass production.